Lichen planus: Oral manifestations, differential diagnosis and treatment - Bradić-Vasić Marija; Pejčić Ana S.; Kostić Milena M.; Minić Ivan Z.; Obradović Radmila R.; Stanković Ivana V. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introduction: Some of the typical skin diseases, such as Pemphigus vulgaris, Pemphigoid mucosae oris, Erythema exudativum multiforme, Sclerodremia, Dermatitis herpetiformis-Duhring and Lichen planus, can cause swelling and irritation in mucous membranes of the oral cavity. Aim: The aim of the study was to precise diagnosis and treatment of oral Lichen planus manifestations. Methods: Analyzing the literature data and the experience of clinicians, the most common oral lichen planus manifestations were investigated. Results: This disease most commonly occurs in middle-aged patients (30-60 years) and is more common in women than in men. Oral Lichen planus is rarely seen in children. The disease presents in 0.5% to 2% of the population. Clinical history established the relation between oral Lichen planus and oral carcinoma, and therefore this disease should be considered a precancerous lesion. Conclusion: Dermatoses in the mouth are localized most often in the oral mucosa, both at the height of the occlusal line and in the mucous membrane of the retromolar area, but they can also occur in the mucous membranes of the tongue, the floor of the mouth and lips.